2015
DOI: 10.1039/c5an01177a
|View full text |Cite
|
Sign up to set email alerts
|

Detection and quantification of the opioid tramadol in urine using surface enhanced Raman scattering

Abstract: There is an on going requirement for the detection and quantification of illicit substances. This is in particular the case for law enforcement where portable screening methods are needed and there has been recent interest in breath tests for a range of narcotics. In this study we first developed surface enhanced Raman scattering (SERS) for the detection of tramadol in water and establish robust and reproducible methods based on silver hydroxylamine colloid. We used 0.5 M NaCl as the aggregating agent, with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…Finally, the detection of drugs of abuse is important and this has been shown using colloidal-based SERS for the quantification of the controlled substance tramadol [38] and the previously categorised legal high 5,6-methylenedioxy-2aminoindane (MDAI) [39]. SERS has also been used to measure drug overdoses from human saliva [40] as well as drugs of abuse [41,42].…”
Section: A Brief Introduction To Sers and Quantitative Analysismentioning
confidence: 99%
“…Finally, the detection of drugs of abuse is important and this has been shown using colloidal-based SERS for the quantification of the controlled substance tramadol [38] and the previously categorised legal high 5,6-methylenedioxy-2aminoindane (MDAI) [39]. SERS has also been used to measure drug overdoses from human saliva [40] as well as drugs of abuse [41,42].…”
Section: A Brief Introduction To Sers and Quantitative Analysismentioning
confidence: 99%
“…Using artificial neural networks (ANNs), it was demonstrated that SERS could be used for simultaneous analysis of multiple determinands without recourse to lengthy chromatography. Detection of the pain reliever tramadol in artificial urine by SERS using suspensions of Ag NPs was also demonstrated [37]. The limit of detection was 657.5 ng mL −1 , which is close to the levels typically found in individuals who use tramadol for pain relief.…”
Section: Resultsmentioning
confidence: 66%
“…These include benzene, toluene, ethylbenzene, and xylenes (BTEX) [2,3,4,5]; polycyclic aromatic hydrocarbons (PAHs) [6,7,8,9]; volatile organic compounds (VOCs) such as chlorinated solvents [3,10] and methyl t-butyl ether (MTBE) [3]; heavy metals [11,12,13,14,15]; toxic or radioactive cations/anions [16,17,18,19,20,21,22,23,24]; ionic nutrients [16,25,26,27]; pesticides [28,29,30,31,32]; drugs and pharmaceuticals [33,34,35,36,37,38]; and explosive materials [39,40,41,42,43]. In addition, SERS has been combined with other analytical techniques such as gas chromatography (GC) [44,45], thin layer chromatography (TLC) [46], liquid chromatography (LC) and flow injection analysis (FIA) [47,48,49], and electrochemistry [50,51].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise a highly sensitive spectroscopic tool offers great potential for drug detection. 35,36 Key to this spectroscopic method is the presence of coinage metal nanoparticles, preferentially gold and silver, 37 but copper is also an applicable SERS substrate. 38,39 Their LSPR, 40 i.e.…”
Section: Introductionmentioning
confidence: 99%